Research Centers for Intelligent Plant Production Systems in Japan (8) Shimane University - ASAO, Toshiki (Shokubutsu Kankyo Kogaku, 2013)
This paper introduces the Plant Factory Research Center in Shimane University. First, the outline of the support and research center for the plant factory in Shimane University is reported. Then, research subjects, training programs for the plant factory is explained, and the contact information is indicated.